2010
DOI: 10.1097/tp.0b013e3181ffba5e
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Pancreatic Islets Transplanted Into the Liver in Humans

Abstract: Pancreatic islets (PI) visualization was safe and successful in all recipients but was less efficient if labeling period was less than 16 hr. Significant decrease of islet spots occurred at week 1, suggesting early islet destruction or impaired engraftment. Afterward, the islet spot numbers remained stable for up to 24 weeks. Data show that MR detection of ferucarbotran-labeled islets enables their long-term noninvasive visualization and correlates with sustained C-peptide production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 25 publications
6
73
1
Order By: Relevance
“…3). Although no independent method was used to confirm this finding, significant C-peptide levels and near-normal HbA1c values were achieved in these patients with a substantial reduction of insulin dose, suggesting that the remaining grafts were functional 104 . Two clinical trials using PET imaging of 18 F-FDG–labeled islets showed early engraftment in the liver 105, 106 .…”
Section: Imaging In Selected Organsmentioning
confidence: 91%
See 2 more Smart Citations
“…3). Although no independent method was used to confirm this finding, significant C-peptide levels and near-normal HbA1c values were achieved in these patients with a substantial reduction of insulin dose, suggesting that the remaining grafts were functional 104 . Two clinical trials using PET imaging of 18 F-FDG–labeled islets showed early engraftment in the liver 105, 106 .…”
Section: Imaging In Selected Organsmentioning
confidence: 91%
“…However, a subsequent trial using ferucarbotran-labeled islets demonstrated a 60% decrease in graft volume one week after transplantation in eight patients by MRI 104 (Fig. 3).…”
Section: Imaging In Selected Organsmentioning
confidence: 96%
See 1 more Smart Citation
“…9,14,70,77 Some of these approaches have also been applied in clinical studies. 47,78,79 These labeling approaches have been intensively reviewed. For more comprehensive reviews on MRI-based cell labeling and visualization techniques, we refer to references 11, 14, 22, 29, 30. The most sensitive approach for the MRI-based cell visualization is the utilization of SPIOs as cell labeling agents (Figure 11.3).…”
Section: Contrast Generation In Mr Spectroscopic Imagingmentioning
confidence: 99%
“…It was shown that, after graft rejection in allogeneic animals, the number of hypointense spots was much reduced over time compare to syngeneic transplants [65, 67, 68]. After the initial MRI cell tracking trials appeared safe [69], MRI islet cell tracking was introduced in the clinic a few years later [70, 71]. However, the initial findings in rodents could not be reproduced, in that the number of MRI-visible spots did not correlate to the initial number of transplanted islets and hence, no good correlation with cell survival could be made.…”
Section: Personalized Treatment Of T1dmmentioning
confidence: 99%